Pertanggungjawaban Hukum Terhadap Penyelenggara Sistem Elektronik Atas Promosi Minuman Beralkohol Berdasarkan Hukum Positif Indonesia - Rifva Putri Abie Sutarya; Enni Soerjati Priowirjanto; Tasya Safiranita (Jurnal Indonesia Sosial Teknologi, 2022)
Instagram platform is used as a media of promoting alcoholic beverages because of its low cost and rapid dissemination of information. However, uploading alcoholic beverage content is against the law because alcoholic beverages cannot be promoted in the mass media, including social media. This study aims to determine how the platform has responsibilities. This research was conducted using a normative juridical approach, that the research was conducted by conducting research through the literature as the main research material. Based on the research conducted, it was found that the legal liability of the Electronic System Operator for the Private Scope of the Instagram Platform is very limited if there is an upload of content that violates the provisions, so that sanctions that can be imposed to suppress the upload of illegal content must be applied to business actors as users of the electronic system.